Manajemen Full Day School untuk Meningkatkan Mutu Madrasah di MTs Negeri 3 Kebumen - Umi Arifah (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2020)
This research is a qualitative descriptive research with a case study approach on the implementation of the Full Day School program at MTs Negeri 3 Kebumen. The data sources for this research consisted of documentation, field visits and interviews with several elements such as: madrasa heads, Full Day School administrators, and teachers. Collection techniques used interview instruments, participatory observation, documentation. The qualitative data analysis technique uses 3 stages, namely 1) data reduction, 2) data display, and 3) data verification. The results of the study can be concluded that the implementation of Full Day School management to improve the quality of madrasas is carried out through four activity processes which include planning, organizing, implementing and supervising. Full Day School management is well implemented as evidenced by the achievements achieved by students through various competitions both in the academic and non-academic fields at various levels including sub-districts, districts, provinces and national events.